Perlindungan Hak Ulayat Masyarakat Adat Dalam Proyek Strategis Nasional (PSN): Studi Kasus Pembangunan Ibu Kota Nusantara (IKN) - Aura, Shandy; Abidin, Muhammad Zaenal (Eastasouth Institute, 2025)
The development of the Nusantara Capital City (IKN) in East Kalimantan is designated as aNational Strategic Project (PSN) through Law Number 3 of 2022 concerning the NusantaraCapital City. Behind the ambition to accelerate development, this project has the potential tothreaten the existence of the customary rights of indigenous peoples who have inhabited thearea for generations, such as the Balik, Paser, and Kutai tribes. This article raises two mainproblems, namely how to protect the customary rights of indigenous peoples in IKNdevelopment projects, and the challenges and obstacles in the implementation of thisprotection. The purpose of this paper is to analyze the effectiveness of existing regulations andpropose solutions to ensure the protection of the rights of indigenous peoples in the context ofPSN development. The research method used is normative juridical with a legislative approachand case studies. In normative studies, it reviews legal instruments such as the UUPA, theForestry Law, and regulations on indigenous peoples that are relevant to the development ofthe IKN. Case studies show overlapping land claims, weak formal legal recognition ofindigenous peoples, and limited participation in decision-making processes. The main obstaclelies in the gap between the country's legal norms and the social realities of indigenous peoples.This article recommends several strategic steps such as strengthening formal recognitionthrough regional regulations, inclusive participatory consultation, and the establishment ofprotection mechanisms that ensure agrarian justice for indigenous peoples in the developmentof the IKN.